Teachers' Verbal Lexical Explanation for Second Language Vocabulary Learning: A Meta‐Analysis. Issue 2 (27th March 2022) - Lee, Jang Ho; Lee, Hansol
Abstract: This article reports a meta‐analysis of studies on the effects of teachers' verbal lexical explanation (TVLE), as one type of lexical focus on form, on second language vocabulary learning. The dataset for this meta‐analysis included 14 studies, representing a total of 36 independent samples ( N = 3, 304). The results of this study reveal that TVLE resulted in more vocabulary gains than an absence of TVLE, at posttest and delayed posttest. In addition, explanation in the first language was more effective than explanation in the second language at posttest and delayed posttest. We further identified a range of potential moderators that may influence the effects of TVLE. In particular, we found that the overall effectiveness of TVLE was greater when the degree of vocabulary knowledge was measured through recall tests rather than through recognition tests in the long term. Abstract :